Numerical Study the Effect of Cylinder Location on the Mixed Convection in an Open Square Cavity - Mohammed, Eman G.; Abood, and Falah A. (Basrah Journal for Engineering Sciences, 2023)
Mixed convection heat transfer of air in a horizontal channel with an open square cavity is studied numerically. At the center of the cavity, it is an insulated rotating circular cylinder for enhancing the efficiency of heat transmission, the location of the inner cylinder is changed vertically along the centerline of the cavity. Heat is applied to the bottom wall of the cavity at a constant temperature, and the other walls are adiabatic. The flow is steady-state, laminar, and incompressible. Using computational fluid dynamics (CFD) and the commercial software program FLUENT 2019 R1, the equations of continuity, momentum, and energy are numerically solved. The angular velocity of the cylinder range is (0 . 5 ≤ ω ≤ 4) rad/sec in a counterclockwise direction, the Richardson number range ( Ri = 0 . 1 , 1 , 10), Reynolds number is 100 and the cylinder location is ( C = 70 , 50 , 30) mm. The airflow Prandtl number is taken as ( Pr = 0 . 7). The effect of various positions of the rotating cylinder has been examined through the visualization of streamline and isotherm contour, as well as the distribution of the average Nusselt number of the heated surface. The results indicate that the flow field and temperature distributions inside the cavity are strongly dependent on the rotating circular cylinder and the position of the inner cylinder.